Thermal Performance of Seaweeds and Seagrasses Across a Regional Climate Gradient - Bennett, Scott; Vaquer-Sunyer, Raquel; Jordá, Gabriel; Forteza, Marina; Roca, Guillem; Marbà, Núria (Frontiers in Marine Science, 2022)
Comparative patterns in thermal performance between populations have fundamental implications for a species thermal sensitivity to warming and extreme events. Despite this, within-species variation in thermal performance is seldom measured. Here we compare thermal performance both within-species and between-species, for two species of seagrass (Posidonia oceanica and Cymodocea nodosa) and two species of seaweed (Padina pavonica and Cystoseira compressa) across the Mediterranean Sea. Experimental populations from four locations representing between 75 and 99% of each species thermal distribution and a 6°C gradient in summer temperatures, were exposed to 10 temperature treatments between 15 and 36°C. Experimental thermal performance displayed the greatest variability between species, with optimal temperatures differing by over 10°C within the same location. Within-species differences in thermal performance were also important for P. oceanica which displayed large thermal safety margins within cool and warm-edge populations and small safety margins within central populations. Our findings suggest patterns of thermal performance in Mediterranean seagrasses and seaweeds retain deep “pre-Mediterranean” evolutionary legacies, suggesting marked differences in sensitivity to warming within and between benthic marine communities.